Interferon-gamma release assay performance in northeastern Brazil: influence of the IFNG + 874 A>T polymorphism - Carneiro,Valdirene Leão (2018)
ABSTRACT Introduction Latent tuberculosis infection diagnosis based on the release of interferon-gamma in cultures of peripheral blood cells stimulated with Mycobacterium tuberculosis antigens has replaced the tuberculin skin test in many countries with low tuberculosis prevalence. The IFN-γ production can be influenced by genetic polymorphisms, of which the IFNG + 874 (rs62559044) locus is the most studied. We investigated the possible influence of the IFNG + 874 A/T polymorphism on interferon-gamma test performance. Methods Patients diagnosed with pulmonary tuberculosis (75), volunteers with positive tuberculin skin test (70) and healthy volunteers with negative tuberculin skin test and no history of contact with tuberculosis (57) were evaluated regarding the IFNG + 874 genotype and the IFN-γ levels in whole blood cultures performed using an interferon-gamma commercial kit (QuantiFERON-TB® Gold In-Tube). Results IFN-γ production was not influenced by the IFNG + 874 genotype, regardless of antigen or mitogen-based stimulation, which suggests that other genes may influence IFN-γ production in response to mycobacteria. The IFNG + 874 polymorphism was found to exert no influence over QFT-IT test sensitivity in our study. Conclusions The IFNG + 874 polymorphism was not shown to influence QuantiFERON-TB® Gold In-Tube test performance in an admixed population from northeastern Brazil.